(3KeHdjfG CejQI GdRghQ (B= Thumbelina princess of flowers (3YQHj (B- Englishs - (3GdSjhaj, gGOjs; Amit, S ((3GdLjRI, eUQs (3GdeDSSI GdYQHjI fGTQhf hehRYhfs)
(3gj bUU gGOaI, ebJHSI ef GdJQGK GdYGdej, hGdJj bGe HJCdjagG GdYOjO ef GdeDdajf GdYGdejjf CeKGd gGfR cQjSJjGf CfOQSf hGdCNhGf LQje hBNQjf, hbO befG HEYGOI UjGZJgG Hbde YQHj MJi JJfGSH eY GdKbGaI hGdbje GdYQHjIs
(3bUU YQHjIs
(3GdfU HGddZJjf GdYQHjI hGdEfLdjRjIs
1 2 5 11 13 14 21
Keywords: (3GdbUU GdYQHjIs